Defending Indigenous Midwifery: Finding a Common Path Among Researchers, Midwives, and Activists. Issue 2 (2nd December 2020) - El Kotni, Mounia
Abstract: In this essay, I reflect on six years of collaboration between myself and an organization of indigenous midwives in Mexico. I interrogate the process of finding common grounds between researchers and activists, which includes building a shared political vision of indigenous midwifery and negotiating disagreements on the different ways to impulse change. Building on my experience with Mexican midwives and activists, I share some of the tools we have used, both from within and outside of academia, to contribute to social change. I build on Shannon Speed's call for a "critically engaged activist research" to raise awareness on the urgency of moving from applied anthropology to activist anthropology.